A Regional Framework for Urban History - Stelter, Gilbert (Urban History Review / Revue d'histoire urbaine, 1985)
Urban history may not have fulfilled the predictions made for it by H J. Dyos because it has limited itself too narrowly to the boundaries of the city itself. A broader regional framework is proposed based on the insights of the traditional metropolis/hinterland concept. Four types of city-region relationships are identified by distinguishing several levels of these relationships: cities and an international urban system; the nation-state as a region; regions within a nation-state; a city and its local hinterland. Examples are chosen from the Canadian, American, Latin American, and Australian urban experiences. An important consequence of this regional approach is that the smaller places, the villages and towns, must also be seen as an integral part of the complex web of population concentrations within a region.